Max Meow. #5, Attack of the Zombees - Gallagher, John, 1967- (New York : Random House, 2023)
"Something strange is going on with Kittyopolis's bees and Max and Mindy need to figure it out to save the bees and Mindy's mom's campaign for Mayor."--
Ages 7-10
Keywords: Superheroes -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Bees -- Comic books, strips, etc; Superhero comics; Action and adventure comics; Graphic novels